2023
DOI: 10.3390/nu15173827
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in Cancer Rehabilitation—A Retrospective Study from a Specialized Clinic

Christina Pfister,
Joerg Schoenemann

Abstract: Background: Micronutrient deficiencies are common at the time of cancer diagnosis and are associated with worse prognosis. Little is known about them in cancer rehabilitation. Methods: Data from routine health-related quality of life (HRQOL) were analyzed at an inpatient cancer rehabilitation center. Rehabilitation patients completed the EORTC QLQ-C30 questionnaire before and after multidisciplinary rehabilitation treatment and three months after discharge. Selenium and zinc status were measured in whole blood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…A study of 271 patients (including PCA) revealed that selenium deficiency was common in PCA patients and that selenium supplementation improved overall quality of life, physical and emotional functions, and fatigue. 53 Therefore, selenium supplementation may improve the prognosis of PCA patients.…”
Section: Seleniummentioning
confidence: 99%
“…A study of 271 patients (including PCA) revealed that selenium deficiency was common in PCA patients and that selenium supplementation improved overall quality of life, physical and emotional functions, and fatigue. 53 Therefore, selenium supplementation may improve the prognosis of PCA patients.…”
Section: Seleniummentioning
confidence: 99%